Development of Fun Polly Games: A Practical Life–Based Learning Media to Enhance Young Children’s Independence - Jhoni Warmansyah; Meliana Sari; Rahayu Yandira S Siregar; Sherly Wiliany; Aisyah Safna (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to develop Fun Polly Games, a Practical Life–based learning media designed to enhance the independence of children aged five to six years in Early Childhood Education settings. The development process followed the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation and employed a mixed-methods approach integrating qualitative techniques such as observations, interviews, and expert validation with quantitative feasibility assessments and comparative testing. The needs analysis indicated a wide gap in children’s independence, as many were not yet able to carry out basic self-help tasks due to the predominance of academic-oriented activities and teacher-centered instructional practices. Teachers also reported that the lack of appropriate learning media hindered efforts to cultivate independence. Expert validation confirmed that Fun Polly Games met the criteria for feasibility, while field trials showed strong positive responses from both children and teachers. The implementation of this media led to improved engagement, richer social interaction, and greater autonomy in performing daily tasks in meaningful contexts. Overall, Fun Polly Games is considered feasible, practical, and contextually relevant as a learning medium capable of strengthening independence-building practices in Early Childhood Education. Aligned with Montessori principles and responsive to contemporary educational needs, this media offers promising potential for supporting long-term independence and character development in young children.